A balance and proprioception intervention programme to enhance combat performance in military personnel. Issue 1 (14th September 2017) - Funk, Shany; Jacob, T; Ben-Dov, D; Yanovich, E; Tirosh, O; Steinberg, N
Abstract : Background: Optimal functioning of the lower extremities under repeated movements on unstable surfaces is essential for military effectiveness. Intervention training to promote proprioceptive ability should be considered in order to limit the risk for musculoskeletal injuries. The aim of this study was to assess the effect of a proprioceptive intervention programme on static and dynamic postural balance among Israel Defense Forces combat soldiers. Methods: Twenty-seven male soldiers, aged 18–20 years, from a physical fitness instructor's course, were randomly divided into two groups matched by age and army unit. The intervention group (INT) underwent 4 weeks of proprioceptive exercises for 10 min daily; the control group underwent 4 weeks of upper body stretching exercises for 10 min daily. All participants were tested pre and postintervention for both static and dynamic postural balance. Results: Significant interaction (condition*pre-post-test*group) was found for static postural balance, indicating that for the INT group, in condition 3 (on an unstable surface—BOSU), the post-test result was significantly better compared with the pretest result (p<0.05). Following intervention, the INT group showed significant correlations between static postural stability in condition 2 (eyes closed) and the dynamic postural stability (length of time walked on the beam following fatigue) ( r ranged from 0.647 to 0.822; p<0.05). Conclusions: The proprioceptive intervention programme for combat soldiers improved static postural balance on unstable surfaces, and improved the correlation between static postural balance in the eyes closed condition and dynamic postural balance following fatigue. Further longitudinal studies are needed to verify the relationship between proprioception programmes, additional weight bearing and the reduction of subsequent injuries in combat soldiers.